2021
DOI: 10.1177/07316844211065183
|View full text |Cite
|
Sign up to set email alerts
|

Light-weight carbon fiber/silver-coated hollow glass spheres/epoxy composites as highly effective electromagnetic interference shielding material

Abstract: Highly effective electromagnetic interference shielding materials with light-weight feature are urgently demanded for releasing electromagnetic pollution. In this study, the hollow glass spheres were coated with silver particles to produce electrically conductive microspheres. The Carbon fiber/silver-coated hollow glass spheres (Ag@HGMs)/epoxy composites were manufactured by composites liquid molding process. The electromagnetic interference shielding properties of the composites were investigated in the X-ban… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…Although this body of research reveals the dependence of mechanical and physical behavior thermosetting composites reinforced with fillers, the use of the hollow glass microspheres (HGMSs) as lightweight high stiff reinforcements has been rarely reported in respect of the elastic response of polyesterbased composites filled with HGMS as the reinforcement [16]. In one study, Chen et al [17] reported the use of HGMSs coated with silver particle aiming at the fabrication of electrically conductive microspheres to be employed as one of the reinforcement phase in epoxybased liquid molded composites. The composites exhibited electromagnetic interference shielding properties whilst the HGMSs acted as materials to fill up the vacancies generated by the network of carbon fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Although this body of research reveals the dependence of mechanical and physical behavior thermosetting composites reinforced with fillers, the use of the hollow glass microspheres (HGMSs) as lightweight high stiff reinforcements has been rarely reported in respect of the elastic response of polyesterbased composites filled with HGMS as the reinforcement [16]. In one study, Chen et al [17] reported the use of HGMSs coated with silver particle aiming at the fabrication of electrically conductive microspheres to be employed as one of the reinforcement phase in epoxybased liquid molded composites. The composites exhibited electromagnetic interference shielding properties whilst the HGMSs acted as materials to fill up the vacancies generated by the network of carbon fibers.…”
Section: Introductionmentioning
confidence: 99%